Verbal and Numerical Ability: Their Correlation with Mathematical Modeling Ability - Sarjana, Ketut; Kertiyani, Ni Made Intan (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study focuses on analyzing the relationship between verbal and numerical abilities in the ability to make mathematical models. The population of this study is junior high school students who use the 2013 curriculum in Mataram City. The research sample was taken with a stratified cluster sampling system. The sample used was 411 students. Data were taken using 3 tests, namely verbal ability test, numerical ability, and ability to make mathematical models. The data was collected using descriptive statistics and inferential statistics, namely multiple linear regression analysis. Descriptive statistics show that more than half of the respondents are in the medium or high category for the three abilities tested. Furthermore, based on the results of inferential statistics, it is found that verbal and numerical abilities have a significant effect on the ability to make mathematical models. The relationship between the three variables, namely Y=0.355X1+0.204 X2-5.446, where Y is the score of the ability to make mathematical models, X1 is the score of verbal ability and X2 is the score of numerical ability. Together, verbal and numeric abilities affect the ability to make mathematical models by 61.2%. Meanwhile, the verbal ability has a direct effect on the ability to make mathematical models at 35.5%. The numerical ability has a direct effect on the ability of mathematical models by 56.6%. The findings imply that enhancing both verbal and numerical abilities at the same time can boost the effectiveness of mathematical models more effectively than enhancing each ability separately.